Changes and transcriptome regulation of endogenous hormones during somatic embryogenesis in Ormosia henryi Prain - Wu, Gaoyin; Wei, Xiaoli; Wang, Xiao; Wei, Yi (Frontiers in Plant Science, 2023)
Ormosia henryi is a rare and endangered plant growing in southern China. Somatic embryo culture is an effective measure for the rapid propagation of O. henryi. It has not been reported how regulatory genes induce somatic embryogenesis by regulating endogenous hormone changes during the process of somatic embryogenesis in O. henryi. In this study, we analysed the endogenous hormone levels and transcriptome data of nonembryogenic callus (NEC), embryogenic callus (EC), globular embryo (GE) and cotyledon embryo (CE) in O. henryi. The results showed that the indole-3-acetic acid (IAA) content was higher and the cytokinins (CKs) content was lower in EC than in NEC, and the gibberellins (GAs) and abscisic acid (ABA) contents were significantly higher in NEC than in EC. The contents of IAA, CKs, GAs and ABA increased significantly with EC development. The expression patterns of differentially expressed genes (DEGs) involved in the biosynthesis and signal transduction of auxin (AUX) (YUCCA and SAUR), CKs (B-ARR), GAs (GA3ox, GA20ox, GID1 and DELLA) and ABA (ZEP, ABA2, AAO3, CYP97A3, PYL and ABF) were consistent with the levels of endogenous hormones during somatic embryogenesis (SE). In this study, 316 different transcription factors (TFs) regulating phytohormones were detected during SE. AUX/IAA were downregulated in the process of EC formation and GE differentiation into CE, but other TFs were upregulated and downregulated. Therefore, we believe that relatively high IAA content and low CKs, GAs and ABA contents contribute to EC formation. The differential expression of AUX, CKs, GAs and ABA biosynthesis and signal transduction genes affected the endogenous hormone levels at different stages of SE in O. henryi. The downregulated expression of AUX/IAA inhibited NEC induction, promoted EC formation and GE differentiation into CE.